1975
DOI: 10.1128/jvi.15.2.322-331.1975
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synthesis of DNA in nuclei isolated from human lung cells infected with herpes simplex type II virus

Abstract: An isolated nuclei system prepared from herpes type II-and mock-infected human embryonic lung cells is able to synthesize cellular and viral DNA in the same proportion as in vivo at various times after infection. Incorporation of [3H ]TTP in the in vitro reaction mixture requires Mg2+ and ATP. Overall in vitro DNA synthesis in nuclei isolated from herpes-infected cells is semiconservative as demonstrated by bromodeoxyuridine-substituted DNA density-transfer experiments, but exhibits a significant fraction of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
10
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
5
10
0
Order By: Relevance
“…All assays were performed in duplicate or triplicate. which permitted linear incorporation for at least 5 rain plus hyperbolic incorporation up to 1 h. A decreasing rate of incorporation in HSV-infected nuclei has been consistently reported by others [9,10,27] and has been shown to be associated with replicative DNA synthesis [13]. The reasons for limited synthesis are unknown but the need to avoid high Mg 2+ concentrations suggests that the DNA product may be degraded by the HSV-induced DNAase(s) which are activated by Mg 2+ [28].…”
Section: Requirements For Dna Synthesissupporting
confidence: 75%
See 1 more Smart Citation
“…All assays were performed in duplicate or triplicate. which permitted linear incorporation for at least 5 rain plus hyperbolic incorporation up to 1 h. A decreasing rate of incorporation in HSV-infected nuclei has been consistently reported by others [9,10,27] and has been shown to be associated with replicative DNA synthesis [13]. The reasons for limited synthesis are unknown but the need to avoid high Mg 2+ concentrations suggests that the DNA product may be degraded by the HSV-induced DNAase(s) which are activated by Mg 2+ [28].…”
Section: Requirements For Dna Synthesissupporting
confidence: 75%
“…The use of isolated nuclei should be very valuable in this regard because the nuclear matrix is intimately involved in DNA replication [2] and in herpes virogenesis [3]. In addition, much of the replication complex -including the natural template and DNA polymerases [4] -is functional [5][6][7][8][9][10][11][12][13].…”
Section: Lnffoductionmentioning
confidence: 99%
“…(iii) Both pseudorabies virus DNA (15) and HSV DNA (17) replicate in a semiconservative fashion. Newly replicated DNAs contain relatively small oligonucleotide fragments, which are repaired and/or ligated on maturation (1,3,7).…”
mentioning
confidence: 99%
“…Newly replicated DNAs contain relatively small oligonucleotide fragments, which are repaired and/or ligated on maturation (1,3,7). Replication of HSV DNA in isolated nuclei is accompanied by extensive repair synthesis (17). (iv) Frenkel et al (5,6) concluded that at least one site of initiation of viral DNA synthesis occurs at or near the terminus of the S component.…”
mentioning
confidence: 99%
“…A number of infected cell preparations supporting the synthesis of herpes simplex virus (HSV) DNA have been described, including disrupted whole infected cells (7), isolated nuclei (7,8,9,10), nuclear monolayers (11), soluble chromatin (12,13,14), and ill-defined complexes released from infected cell nuclei (15,16). Most of these, however, fail to synthesize unit size viral DNA or to support semi-conservative replication, and none has been shown to incorporate precursors into the large concatemers thought to be the primary templates for HSV DNA replication (17,18).…”
Section: Introductionmentioning
confidence: 99%